2016
DOI: 10.1007/s00261-015-0632-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of filtered back projection and iterative reconstruction in diagnosing appendicitis at 2-mSv CT

Abstract: When diagnosing appendicitis at 2-mSv CT in adolescents and young adults, FBP and IR were comparable in radiologists' diagnostic performance and confidence while IR exhibited higher subjective image quality than FBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Willingness was not significantly associated with the use of iterative reconstruction. Previous studies have not shown significant clinical or diagnostic advantages of iterative reconstruction techniques in 2-mSv appendiceal CT (10,18). However, newer iterative reconstruction techniques may show more obvious advantages in the future, particularly at even lower radiation doses.…”
Section: Discussionmentioning
confidence: 98%
“…Willingness was not significantly associated with the use of iterative reconstruction. Previous studies have not shown significant clinical or diagnostic advantages of iterative reconstruction techniques in 2-mSv appendiceal CT (10,18). However, newer iterative reconstruction techniques may show more obvious advantages in the future, particularly at even lower radiation doses.…”
Section: Discussionmentioning
confidence: 98%
“…In subsequent studies comparing LDCT and CDCT [ 37 38 39 40 41 42 43 ], the tested low dose ranged from 1 mSv to 4 mSv, while the tested conventional dose ranged from 5 mSv to 10 mSv, with a 2–6 fold difference between the low and conventional doses within each of the studies. In recent comparative studies [ 41 42 43 44 ], the tested low dose ranged from 1 to 2 mSv, which was similar to the radiation level tested by Keyzer et al [ 36 ]. In non-comparative studies that explored the usefulness of LDCT in the diagnosis of appendicitis [ 45 46 ], the tested low dose also ranged from 1 to 2 mSv, which is close to the worldwide average annual exposure to natural radiation sources [ 47 ] or dose of three conventional abdominal radiographs [ 27 ].…”
Section: Ct Radiation Dosementioning
confidence: 56%
“…Gastric cancer can be divided into early gastric cancer and advanced gastric cancer. Its CT has various manifestations, such as early gastric cancer is difficult to detect on CT due to its small lesions, and gastroscopic examination is required for diagnosis at this time [ 19 ]. For advanced gastric cancer, the cancer has invaded the submucosal layer and even entered the muscularis.…”
Section: Discussionmentioning
confidence: 99%